Recurrent reproductive failure and celiac genetic susceptibility, a leading role of gluten - de la Fuente-Munoz, Eduardo; Fernández-Arquero, Miguel; Subhi-Issa, Nabil; Guevara-Hoyer, Kissy; Suárez, Lydia Pilar; Laborda, Raquel Gil; Sánchez, Marina; Ochoa-Grullón, Juliana; Guzmán-Fulgencio, María; Villegas, Ángela; Mansilla, María Dolores; Pérez, Noelia; et al. (Frontiers in Immunology, 2024)
Introduction: The prevalence of gluten-related disorders, mainly celiac disease (CD) and non-celiac gluten sensitivity (NCGS), varies between 0.6% and 13% in the general population. There is controversial evidence regarding the association of both CD and NCGS with extra-digestive manifestations, including recurrent reproductive failure (RRF), which may have clinical implications. Objective: To study the prevalence of HLA susceptibility alleles for CD/NCGS in a cohort of female patients with RRF from a single reference center and to evaluate the effect of a gluten-free diet on reproductive success. Material and methods: A retrospective study was conducted on 173 patients with RRF, consecutively attended at the Reproductive Immunology Unit of San Carlos University Clinical Hospital in Madrid. We collected and analyzed the clinical, analytical, and immunological profiles of RRF patients who presented HLA alleles associated with CD and NCGS (HLA DQ2.2, DQ2.5, DQ8, and DQ7.5). Results: We observed a significantly higher prevalence of HLA alleles associated with CD and NCGS in our RRF cohort compared to the prevalence in the general population (69% versus 35-40%, p<0.0001). Only 2.3% of patients met the criteria for a CD diagnosis. In our RRF cohort, HLA-genetic susceptibility for CD/NCGS (HLA-risk Group) was associated with a significantly higher rate of hypothyroidism compared to patients without these alleles (HLA-negative Group) (48.7% versus 26.92%), p=0.03). Patients with HLA-genetic susceptibility for CD/NCGS and thyroid disease had a significantly higher success rate in the subsequent pregnancy after management (55% versus 30%, p=0.002). Two factors were found to be significant in this group: a gluten-free diet (p=0.019) and the use of levothyroxine (p=0.042). Conclusions: In our cohort of RRF patients, we observed a significantly higher prevalence of HLA susceptibility genes for CD/NCGS compared to the general population, also associated with a higher incidence of thyroid alterations. A gluten-free diet and the use of levothyroxine in cases of thyroid pathology had significant beneficial effects on pregnancy outcomes. We suggest that HLA typing for CD/NCGS and a gluten-free diet, in the presence of risk alleles, can improve pregnancy outcomes in RRF patients.